Cascade cyclization of glycine derivatives with β-ketoesters for polysubstituted 1, 4-dihydropyridines by visible light photoredox catalysis. Issue 33 (14th August 2020) - Zhu, Xiao; Zhu, Zhi-Qiang; Guo, Dong; Liu, Shan; Ji, Jiu-Jian; Tang, Juan; Yuan, En; Xie, Zong-Bo; Le, Zhang-Gao
Abstract: Visible light photocatalytic cascade cyclization reaction between glycine derivatives and β -ketoesters using Ir (ppy)3 as a catalyst and dicumyl peroxide (DCP) as an oxidant was described. A series of N -aryl glycine esters proceeded the cyclization smoothly with β-ketoesters at room temperature, affording the desired 1, 4-dihydropyridines (1, 4-DHPs) in satisfactory yields. A possible mechanism for the cascade cyclization reaction by visible light photoredox catalysis was also proposed. This protocol not only provides an efficient and convenient approach to synthetize various 1, 4-dihydropyridines, but also has potential utilities for the construction of bioactive molecules. Graphical abstract: Visible light photocatalytic cascade cyclization reaction between glycine derivatives and β -ketoesters using Ir (ppy)3 as a catalyst and dicumyl peroxide (DCP) as an oxidant was described. A series of N -aryl glycine esters proceeded the cyclization smoothly with β-ketoesters at room temperature, affording the desired 1, 4-dihydropyridines (1, 4-DHPs) in satisfactory yields. A possible mechanism for the cascade cyclization reaction by visible light photoredox catalysis was also proposed. This protocol not only provides an efficient and convenient approach to synthetize various 1, 4-dihydropyridines, but also has potential utilities for the construction of bioactive molecules. Image 1 Highlights: Visible light photocatalytic cascade cyclization of N -aryl glycine esters with  β -ketoesters to afford diverse polysubstituted 1, 4-dihydropyridines at room temperature was disclosed. A possible reaction mechanism for the cascade cyclization by visible light photoredox catalysis was proposed on the basis of control experiments. The synthetic protocol features good functional group tolerance, mild conditions and simple operation.